Pengaruh Auditori Verbal Therapy Terhadap Kemampuan Penguasaan Kosa Kata Pada Anak Yang Mengalami Gangguan Pendengaran - H, Hermin Ratih; Rini, Rr Amanda Pasca (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2015)
Research methods quasi experiment on students TKLB especially children with hearing loss is aimed to prove the effect of treatment or therapy AVT toward mastery of vocabulary in children who have a hearing loss. Research data collection using a check list or learning outcomes assessment sheet that refers to the criteria set out in the curriculum in 2006. Evidence hypothesis through non-parametric Wilcoxon test test obtained value Z = -3.934; p = 0.000 (p <0.01), which means no influence on the ability Auditory Verbal Terapy vocabulary in children who have a hearing loss.Through the process of AVT therapy can be seen that the vocabulary of children already covers almost the entire class of existing words. Of the eight classes of existing words, most of the child's vocabulary already includes a noun, verb (the verb), adjectives, description (adverb), pronouns, numbers (Numeral), prepositions, and conjunctions.